WHAT IF PRICES CHANGE? ANALYSIS OF INTERNATIONAL TOURIST MARKET SEGMENTS' COMPOSITION IN THE FACE OF INFLATION FLUCTUATIONS - Jesús Barreal Pernas; Julio Vena Oya; Juan Antonio Parilla González (Cuadernos de Turismo)
The Changes Price Index has considerable volatility that makes massive changes in the global market; subsequently, it could affect tourism demand and transform visitor profiles. The paper aims to answer the effect of it on international tourists and know the segment(s) beneficiated by this context. The research also considers that the CPI is inhomogeneous and involves different types to expand the analysis. The analysis will run a Latent Class model over the international tourist survey data conducted by the Spanish Statistic Office, first to obtain the clusters and later to analyze the elasticity of exogenous variables over the groups. The results show how low-expenditure profile is more sensitive to price changes; meanwhile, others with more added value are more inelastic. The main conclusion is that the business focused on the sun and sand segment and low expenses should adapt their supply by increasing the international tourist perceived value.